Unpacking Ethical Leadership Practices and Governance Strategies of Public Elementary School Principals in the Fourth Congressional District of Quezon: Teachers’ Empirical Insights and Learner Outcomes - Jeansen C. Cabungcal (International Journal of Research Publications, 2026)
This study examined the ethical leadership practices and governance strategies of public elementary school principals in the Fourth Congressional District of Quezon and their influence on learner outcomes. Employing mixed-methods research design, the study involved a total of 181 teachers who participated in the survey, while 10 teachers were involved in in-depth interviews for the qualitative phase. Quantitative data were analyzed using descriptive statistics and Pearson correlation, while qualitative data were thematically analyzed. Findings revealed that teachers perceived their principals’ ethical leadership practices in terms of integrity and fairness, professional role modeling, and accountability and transparency to be at a high level. Governance strategies, particularly in instructional supervision, stakeholder engagement, and resource management, were also widely practiced. Furthermore, teachers reported that ethical leadership significantly influenced learner outcomes, including academic performance, behavior and discipline, and motivation and participation. Correlation analysis confirmed that ethical leadership practices and governance strategies were significantly related to learner outcomes. Qualitative findings supported these results, highlighting that school heads demonstrate fairness, transparency, and adaptability in addressing challenges, though they also encounter constraints such as limited resources, policy ambiguities, and stakeholder pressures. Ethical decision-making was found to be grounded in policy adherence, consultation, and open communication. The study concludes that strong ethical leadership and effective governance practices contribute to improved learner outcomes and positive school climate. It recommends strengthening leadership development programs, enhancing policy clarity, and promoting collaborative governance to further improve educational quality in public elementary schools.